Highly expressed genes in marine sponge Suberites domuncula prefer C- and G-ending codons - Perina, Drago (Array, 2009)
Summary: Sponges are the simplest extant phylum of Metazoa; they are closest to the common ancestor of all multicellular animals. A total of 223 coding sequences from Suberites domuncula (Demospongiae) represent the dataset for the codon usage analysis. A total of 46038 codons had an average guanine and cytosine (G+C) content of 45.8 % and an average content of guanine and cytosine at the synonymous third position of codons (GC3S) of 43.4 %. In this sample of genes considerable variations in synonymous codon usage were found. The G+C content of the coding sequences varied from 34 to 56.1 % and GC3S from 19 to 58.7 %. Correspondence analysis revealed that highly expressed genes preferentially use a limited subset of codons (preferred codons). A total of 15 preferred codons were found and they all, with one exception, end with C or G. The preferential use of C- or G-ending codons in highly expressed genes was possibly developed in a common ancestor of sponges and other Metazoa and it has remained conserved throughout the sponge evolution